The Impact of a Pharmacist Driven 48-hour Antibiotic Time Out during Multi-disciplinary Rounds on Antibiotic Utilization in a Community Non-teaching Hospital. (4th October 2017) - Vasina, Logan; Dehner, Matthew; Wong, Angie; Bojak, Shiva; Dhoot, Sharan; Shaw, David; Jain, Kanu; Gardner, Steven; Chinn, Raymond
Abstract: Background: An antibiotic time out (ATO) at 48–72 hours is a critical component of antimicrobial stewardship programs to improve judicious antibiotic use. It is a strategy to prompt clinicians to re-evaluate antibiotic appropriateness including the need for de-escalation and discontinuation. Sharp Memorial Hospital is a tertiary community hospital with 437 beds and 48 Intensive Care Unit (ICU) beds. In May 2016, an ATO program was initiated in the ICU along with the implementation of multidisciplinary daily Medical ICU rounds 5 days a week led by an intensivist. Methods: We conducted a pre- and post-intervention study to assess the impact of an ATO on utilization of targeted antibiotics (see Table 1). Pharmacists received mandatory education on the components of an ATO, a reference guidebook, and completed a baseline competency prior to ATO implementation. An on demand report was used to identify patients on antibiotic day > 2. A form prompting review of indication, culture results, de-escalation, treatment duration and proton-pump inhibitor appropriateness was completed as part of the daily workflow. Interventions were discussed during rounds or by contacting the physician. Metrics included days of therapy (DOT) per 1, 000 patient days, and intervention numbers, types, and acceptance rates (AR) during two 9-month periods: pre- and post-implementation. Results: There were 829 interventions during the post-implementation period with a 96% AR compared with 83 during the pre-intervention period with a 94% AR. Antibiotic discontinuations and de-escalations comprised 52% of accepted interventions. There was a significant reduction in the use of vancomycin and quinolones with no change in anti-pseudomonal β-lactam use (see Table 1). Conclusion: A pharmacist driven ATO with physician support during multidisciplinary daily rounds reduced antibiotic use and could be expanded house-wide. This strategy could serve as a model to improve antimicrobial stewardship in community, non-teaching hospitals. Disclosures: All authors: No reported disclosures.